Case Report: Infective endocarditis following arteriovenous graft in a peritoneal dialysis patient - Huang, Fangzhong; Zhang, Xingzhen; Xu, Xuchun; Ying, Jun; Fan, Qiuping; Li, Shuangqing; Huang, Jian (Frontiers in Cardiovascular Medicine, 2025)
Infective endocarditis (IE) is a severe and frequently fatal complication in dialysis patients, particularly those with vascular access devices such as arteriovenous grafts (AVGs) or fistulas. We describe the case of a 55-year-old male with end-stage renal disease (ESRD) on peritoneal dialysis (PD), who developed advanced IE following repeated punctures of an AVG. The patient initially presented with fever, erythema, and swelling at the graft site, which progressed to bacteremia due to Staphylococcus aureus. Despite completing a full course of antibiotics and undergoing both mitral and aortic valve replacement, the patient suffered recurrent episodes of acute heart failure requiring repeated hospital admissions. This rare case highlights the substantial risk of IE in dialysis patients with vascular access devices and the importance of early detection and timely intervention. The clinical difficulties and economic strain associated with IE management in this population point to the need for close surveillance, rapid diagnosis, and individualized treatment plans to improve outcomes and control healthcare expenditures.